Jihadism au rebours: Orientalism and Occidentalism for a Counter-Hegemonic Liberation Theology - Demichelis, Marco (Journal of religious history, 2021)
Following its colonial project, Western Europe imposed a political and cultural understanding of state nationalism and religious homogeneity on the entire world in the nineteenth and twentieth centuries. In parallel with this twofold process, “Religious Nationalism” emerged during the Cold War, affecting the Middle East and framing an updated Abrahamic version of religious supremacism: Wahhabi Islam, the Iranian Revolution, and Israeli Orthodox Judaism were politically backed, becoming the frontrunners of a new Global-Religious narrative of conflict. This article aims to critically analyse the Western-Islamic manipulation of “Jihadism” as an artificial and fabricated product, starting from the “deconstruction” of Jihad-Jihadism as an anti-hegemonic narrative. The anti-colonial “Islamic” framework of resistance to the Empire (United States) has effectively adopted the same colonial methodology: using violence and sectarianism in trying to reach its goals. Is the Islamic Supremacist “narrative” more influenced by Western thought than by a real understanding of Islam? At the same time, this article aims to stress the historical reasons why the Arab world has been artificially affected by a peculiar form of “Religious Revanchism” which can be understood only if O. Roy's Holy Ignorance dialogues with Steve Biko's Consciousness in emphasising the need for an updated Islamic Liberation Theology.